2016
DOI: 10.1080/15412555.2016.1220513
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Patients Admitted for Concurrent COPD Exacerbation and Pneumonia

Abstract: It is unclear whether concurrent pneumonia and chronic obstructive pulmonary disease (COPD) have a higher mortality than either condition alone. Further, it is unknown how this interaction changes over time. We explored the effect of pneumonia and COPD on inpatient, 30-day and overall mortality. We used a Veterans Health Affairs database to compare patients who were hospitalized for a COPD exacerbation without pneumonia (AECOPD), patients hospitalized for pneumonia without COPD (PNA) and patients hospitalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…However, it is noteworthy that the decrease in survival begins to occur at 18 months from the first episode of pneumonia. This finding is consistent with those of the two previously cited studies [14,15], since there was no association between pneumonia and increased mortality at 30 days, although an association was found in the long term, possibly owing to COPD itself more than to pneumonia. This observation could be explained by the possibility that, despite being an acute disease, pneumonia leads to the deterioration of symptoms and quality of life in patients with COPD [16], which may not be fully recovered after resolution of pneumonia, thus leading to poorer long-term progress.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, it is noteworthy that the decrease in survival begins to occur at 18 months from the first episode of pneumonia. This finding is consistent with those of the two previously cited studies [14,15], since there was no association between pneumonia and increased mortality at 30 days, although an association was found in the long term, possibly owing to COPD itself more than to pneumonia. This observation could be explained by the possibility that, despite being an acute disease, pneumonia leads to the deterioration of symptoms and quality of life in patients with COPD [16], which may not be fully recovered after resolution of pneumonia, thus leading to poorer long-term progress.…”
Section: Discussionsupporting
confidence: 93%
“…In their study on community-acquired pneumonia (CAP) in patients with and without COPD, Bonnesen et al [14] concluded that the presence of COPD is not a risk factor for mortality at 30 days in patients who have had an episode of community-acquired pneumonia. In contrast, Sharafkhaneh et al [15], who performed a similar study, proposed that pneumonia and COPD affect short-and long-term mortality differently, with pneumonia having a greater short-term effect, and COPD a greater long-term effect.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…1 In addition, pneumonia is often the direct cause of death ascribed to other common causes, such as Alzheimer's disease, lung cancer, and chronic obstructive lung disease. [16][17][18] Figure 1 illustrates the difficulty in improving mortality due to CAP. Pneumonia and influenza have remained in the top 10 causes of death in the US since 1900.…”
Section: Incidencementioning
confidence: 99%
“…40 Infection is known to be a provoking factor for VTE, 41 and concomitant respiratory infection increases the mortality risk in COPD patients. 42 Moreover, COPD represents a chronic inflammatory state which may influence the risk of adverse outcome. 43 In our study, the impact of COPD on VTE-related mortality was neither explained by concomitant cancer, infections, nor arterial cardiovascular diseases since the risk estimates of VTE-related mortality remained essentially unchanged when active cancer, acute medical conditions, and a history of MI and stroke were included in the adjustment models.…”
Section: Discussionmentioning
confidence: 99%